Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Perumahan PT.Hasanah Mulia Investama - Nurul Kumala, Firza Oktavia; Anwar, Moch. Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2020)
The development of the property sector business in Surabaya is quite rapid, signaling an economic improvement towards a better future. These conditions make competition between developers. The competition made PT Hasanah Mulia Investama consider product quality and price with the aim of increasing purchasing decisions that are closely related to consumer behavior which is an important element that must be known by the company. Prompts in Islam in terms of purchasing decisions, consumers should consider the use of goods not only as a desire to satisfy. This research aims to determine the effect of price and product quality on PT Hasanah Mulia Investama's housing purchase decisions and views on the Islamic economy. This research method is quantitative and multiple linear regression analysis techniques and questionnaires as instruments for collecting respondents with a sample size of 38 people. The results showed that partially and simultaneously the price and quality of products affected the purchasing decisions at PT Hasanah Mulia Investama.